Quantum Cosmology and the Wavefunction of the Universe Explorations in minisuperspace, eternal inflation, and topological defects - Fanaras, Georgios (Tufts University Tisch Library, 2026)
Thesis (Ph.D.)--Tufts University, 2025.; Submitted to the Dept. of Physics.; Advisor: Alexander Vilenkin.; Committee: Mark Hertzberg, Lawrence Ford, Krzysztof Sliwa, Jaume Garriga Torres, and Soubhik Kumar.; Keyword: Physics